Is there brief temporal buffering of successive visual inputs? - Smith, W; Mollon, J; Bhardwaj, R; Smithson, H (2011)
The part-report advantage has been used to identify short-lived forms of visual storage (Sperling, 1960). We adopt the part-report paradigm to test whether visual memory can preserve, for a brief time, successive inputs and their temporal order. In our experiments, two successive arrays, each of 4 digits, were presented on each trial. The two arrays were spatially coincident, and each was followed by a random pattern-mask. In the part-report conditions, an auditory cue indicated whether the participant should report the first array or the second array. The results consistently showed a part-report advantage, which ranged in size from 16% to 37%. Delaying the cue by 500 ms abolished most of this advantage, in that performance was then similar to that in whole-report conditions. Subsequent experiments confirmed that the part-report superiority we measure is not achieved by (a) making eye movements that spatially displace the second array relative to the first; (b) extracting information from a single snapshot containing an integrated representation of the targets and masks; or (c) transferring a subset of material to a phonological store. We propose instead that observers have access to a limited, rapidly decaying representation of successive visual inputs stored in temporal sequence.